Self-Inflicted Urethrovesical Foreign Bodies in Children - Canan Ceran; Sema Uguralp (Case Reports in Urology)
We present two cases of self-inflicted urethrovesical foreign body in children. Case 1 was a 6-year-old girl admitted with a history of self-introduction of a pin. The X-ray revealed the pin as 3.5 cm in length and in the bladder. The foreign body was removed endoscopically. Case 2 was a 13-year-old boy with a self-introduced packing needle, 13 cm in length, partially in the urethra. The end and the tip of the needle passed through the urethra to the surrounding tissues. Foreign body removed via a little skin incision with endoscopic guidance. Foreign bodies are rarely found in the lower urinary tract of children. Definitive treatment is usually the endoscopic removal; however, sometimes surgical intervention may require.